Population dynamics in India : with reference to Uttar Pradesh - Dubey, R. M. (Rishi Mani), 1946- (Chugh Publications, 1981)
Study of Kanpur, Agra, Varanasi, Allahabad and Lucknow, based upon 1961 data.